2017
DOI: 10.1021/acsomega.6b00489
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde Detection in Electronic Cigarette Aerosols

Abstract: Acetaldehyde, acrolein, and formaldehyde are the principal toxic aldehydes present in cigarette smoke and contribute to the risk of cardiovascular disease and noncancerous pulmonary disease. The rapid growth of the use of electronic cigarettes (e-cigarettes) has raised concerns over emissions of these harmful aldehydes. This work determines emissions of these aldehydes in both free and bound (aldehyde–hemiacetal) forms and other carbonyls from the use of e-cigarettes. A novel silicon microreactor with a coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(169 citation statements)
references
References 42 publications
12
154
0
3
Order By: Relevance
“…In addition to sampling and analysis, many chemical (e.g., acidity) and physical factors can influence the levels and identities of PG and GLY degradation products, including the proportion of hemiacetal to free HCHO. Finally, the finding that there is a significant relative abundance of 1a – d to HCHO in e-cigarette aerosols, in general agreement with another recent report 3 , coupled with the fact that 1a – d are not well-accounted for as HCHO equivalents via widely used analytical methods, necessitates broader investigation. The further study of 1a – d as well as other challenging e-cigarette aerosol toxins, including acrolein and acetaldehyde, will be reported in due course.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…In addition to sampling and analysis, many chemical (e.g., acidity) and physical factors can influence the levels and identities of PG and GLY degradation products, including the proportion of hemiacetal to free HCHO. Finally, the finding that there is a significant relative abundance of 1a – d to HCHO in e-cigarette aerosols, in general agreement with another recent report 3 , coupled with the fact that 1a – d are not well-accounted for as HCHO equivalents via widely used analytical methods, necessitates broader investigation. The further study of 1a – d as well as other challenging e-cigarette aerosol toxins, including acrolein and acetaldehyde, will be reported in due course.…”
Section: Resultssupporting
confidence: 82%
“…In a more recent investigation, we showed that 1a – d can form under relatively benign, single puff conditions 8 . During the preparation of this manuscript, another significant report appeared showing that 1a – d levels were indeed a potentially concerning proportion of the total HCHO (in the 22–45% range) found in e-cigarette aerosols, specifically when using newer devices possessing increasingly higher power output capabilities 3 . However, as is shown herein, the relative levels of 1a–d to HCHO produced by e-cigarettes can be even higher, because they are dependent on many key variables such as sampling and analytical techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence that the large differentials found here between the cancer potencies of most ECs and those of tobacco smoke may be less for other medical conditions involving the cardiovascular and respiratory systems 37. Future research should address these gaps.…”
Section: Discussionmentioning
confidence: 85%
“…[91][92][93][94][95] A link between e-cigarette use and risk stems from the presence of harmful and potentially harmful constituents identified in aerosols of e-cigs, including metals, particles, carbonyls and flavoring compounds. 71,79,[96][97][98][99][100] However, the presence of toxic carbonyl compounds in e-cigarette aerosols derived from humectants and/or flavoring chemicals used in e-liquid formulations is raising health concerns. 98,101 In order to address these concerns, we set out to measure the generation of carbonyl compounds from the humectants propylene glycol and glycerol, as well as from commercial e-liquids containing flavoring chemicals in "tank type" refillable e-cigarette devices.…”
Section: Significance Of Carbonlys In Electronic Cigarettesmentioning
confidence: 99%